On the catalytic and degradative role of oxygen-containing groups on carbon electrode in non-aqueous ORR - Inozemtseva, Alina I.; Kataev, Elmar; Frolov, Alexander S.; Amati, Matteo; Gregoratti, Luca; Beranová, Klára; Dieste, Virginia Pérez; Escudero, Carlos; Fedorov, Alexander; Tarasov, Artem V.; Usachov, Dmitry Yu; Vyalikh, Denis V.; et al. (Carbon, 2021)
Oxygen reduction reaction (ORR) is a crucial process that drives the operation of several energy storage devices. ORR can proceed on the neat carbon surface in the absence of a catalyst, and its electrochemical activity is determined by its microstructure and chemical composition. Oxygen functional groups unavoidably existing on the carbon surface can serve as adsorption sites for ORR intermediates; the presence of some oxygen functionalities gives rise to an increase in the density of electronic states (DOS) at the Fermi level (FL). Both factors should have a positive impact on the electron transfer rate that was demonstrated for ORR in aqueous media. To study the O-groups effect on the aprotic ORR, which is now of interest due to the extensive development of aprotic metal-air batteries, we use model oxidized carbon electrodes (HOPG and single-layer graphene). We demonstrate that oxygen functionalities (epoxy, carbonyl, and lactone) do not affect the rate of one-electron oxygen reduction in aprotic media in the absence of metal cations since their introduction practically does not increase DOS at FL. However, in Li+-containing electrolytes, oxygen groups enhance both the rate of second electron transfer and carbon degradation due to its oxidation by LiO2 yielding carbonate species.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Graphene; Li–O2 batteries; Oxygen functionalities; Oxygen reduction